Pengaruh Model Pembelajaran Problem Based Learning (PBL) V ariasi dengan Jiksaw Pada Hasil Belajar Redoks Kelas X SMA Negeri 2 Tompaso - Simbawa, Maria S. E.; Lumingkewas, Sonny; Kumajas, Jenny (General Chemistry Journal, 2024)
The problem-based learning model with Jiksaw is a learning model that encourages students to be more active in learning. This research was conducted using a variation of the problem-based learning model with jiksaw which aims to determine student learning outcomes using this learning model. The research method used is an experimental design with a quasi-experimental design, and the form of the design is nonequivalent control group design. the sample used was 11 students in the control class and 10 students in the experimental class. The data collection technique used in this study was using tests, tests in this case pretest and posttest. Based on the results of the normality test calculations, the results are: Pretest experimental class L count -0.022, L table 0.258 data is normally distributed. Pretest control class L count 0.1694, L table 0.249 data normally distributed. The results of the pretest homogeneity test for the experimental class and control class F count 3 and F table 3.0204 so that both classes are homogeneous. The results obtained from the t-test with the results of the posttest t count of 5,535 are greater than the t table of 2,093 with the conclusion that H 0 is rejected so that H 1 is accepted. So it can be concluded that there is an influence on student learning outcomes using the problem-based learning model variation with Jiksaw on the redox learning outcomes of class X SMA Negeri 2 Tompaso.